The tyranny of the head office? Revisiting corporate headquarters' (CHQs) role in MNE subsidiary initiatives - Alain Verbeke; Wenlong Yuan (Journal of Organization Design, 2020)
What roles should corporate headquarters (CHQs) of multinational enterprises (MNEs) play in foreign subsidiary initiatives? Rather than viewing the MNE's CHQ as a single, internally homogenous unit, we call for examining the diversity of individual decision-makers who can be driven by a variety of motivations and have different abilities. Motivations and abilities together determine whether or not corporate executives will choose to intervene in subsidiary initiatives and the effectiveness of such intervention. If dysfunctional, the "tyranny of the head office" materializes. We apply the Coleman-boat concept to show how contextual analyses at the MNE level and the proposed analyses of individual decision-makers need to be combined when exploring the underlying micro-foundational mechanisms of decisions.
Keywords: 650; Subsidiary initiative; Multinational enterprise; Corporate headquarters; Tyranny of the head office; Micro-foundations